Heroes and Villains - David R. Marples (Central European University Press, 2007)
Certain to engender debate in the media, especially in Ukraine itself, as well as the academic community. Using a wide selection of newspapers, journals, monographs, and school textbooks from different regions of the country, the book examines the sensitive issue of the changing perspectives - often shifting 180 degrees - on several events discussed in the new narratives of the Stalin years published in the Ukraine since the late Gorbachev period until 2005. These events were pivotal to Ukrai...